HDE 344787, THE POLARIS ANALOGUE THAT IS EVEN MORE INTERESTING THAN POLARIS - Turner, D. G.; Majaess, D. J.; Lane, D. J.; Percy, J. R.; English, D. A.; Huziak, R. (Одеські астрономічні публікації, 2010)
A collection of active photometric observations over the last half decade, archival data from the past 120 years, radial velocity observations from 1984, and recent monitoring through a pro-am collaboration reveal that the 9th magnitude F9 Ib supergiant HDE 344787 is a double-mode Cepheid variable of extremely small amplitude. It displays remarkably similar, but much more extreme, properties to the exotic Cepheid Polaris, including a rapidlyincreasing period and sinusoidal light variations of decreasing amplitude suggesting that pulsational stability may occur as early as 2045. Unlike Polaris, HDE 344787 displays sinusoidal light variations at periods of both 5d.4 and 3d.8 days, corresponding to canonical fundamental mode and overtone pulsation. But it may be similar to Polaris in helping to define a small subgroup of Cepheids that display characteristics consistent with a first crossing of the instability strip. An update of 2010 observations of this remarkable star is presented.